Training on Simple Determination of Acid Numbers for Students of SMK 01 Palangkaraya: Pelatihan Penentuan Bilangan Asam secara Sederhana untuk Siswa SMK 01 Palangkaraya - Ni'mah, Fatchiyatun (NAWASENA : JOURNAL OF COMMUNITY SERVICE, 2023)
Students who are educated at Vocational High Schools (SMK) are a group that is expected to have strong practical capabilities, prioritizing the development of direct skills in certain fields of expertise in preparation for careers in the industrial world or further appropriate studies. The Energy-Biomass Engineering Department at SMK 01 Palangkaraya is one of the SMK majors that has promising opportunities, especially in Kalimantan which has various potentials in the field of energy and biomass. One of the skills that graduates of the biomass energy engineering program are expected to master is assessing oil quality through knowledge of numbers. As an effort to increase understanding related to acid number determination, a community service was conducted in the form of training on acid number determination. The hands-on training method was chosen due to its ability to provide direct demonstration and practical experience to participants. The results of this service activity showed a significant increase in understanding of the process of determining acid numbers using the titration method, indicating the success of efforts to increase competence in this field.